2010
DOI: 10.1007/s11162-010-9175-2
|View full text |Cite
|
Sign up to set email alerts
|

Do College Students Who Identify with a Privileged Religion Experience Greater Spiritual Development? Exploring Individual and Institutional Dynamics

Abstract: College student spiritual development constitutes an important, yet understudied topic in higher education research. In particular, very little is known about whether and how this development varies among students from diverse religious backgrounds. Using a longitudinal sample of 14,527 students from 136 institutions, the current study explored the degree to which spiritual development is related to the religious affiliations of students and the type of colleges and universities they attend. Hierarchical linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 26 publications
4
35
0
Order By: Relevance
“…Aligned with recent evidence that students' religion/worldview shapes how they perceive and experience their campus and change while in college (Bowman, Felix, & Ortis, 2014;Bowman & Small, 2010, 2012Bowman & Toms Smedley, 2013;Bryant, 2011;Bryant Rockenbach & Mayhew, 2013, 2014Mayhew, 2012;Mayhew et al, 2014;Mayhew & Bryant Rockenbach, 2012), this study supports the assertion that unique spiritual meanings are apparent for different worldview identities. Essential meanings of spirituality, universal to all students, are only part of the story.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Aligned with recent evidence that students' religion/worldview shapes how they perceive and experience their campus and change while in college (Bowman, Felix, & Ortis, 2014;Bowman & Small, 2010, 2012Bowman & Toms Smedley, 2013;Bryant, 2011;Bryant Rockenbach & Mayhew, 2013, 2014Mayhew, 2012;Mayhew et al, 2014;Mayhew & Bryant Rockenbach, 2012), this study supports the assertion that unique spiritual meanings are apparent for different worldview identities. Essential meanings of spirituality, universal to all students, are only part of the story.…”
Section: Discussionsupporting
confidence: 81%
“…The influence of college environments and experiences is not entirely uniform. An emerging stream of scholarship demonstrates students' religion/worldview influences how they perceive and experience their campus and whether and how these experiences encourage spiritual growth (Bowman, Felix, & Ortis, 2014;Bowman & Small, 2010, 2012Bowman & Toms Smedley, 2013;Bryant, 2011;Bryant Rockenbach & Mayhew, 2013, 2014Mayhew, 2012;Mayhew, Bowman, & Bryant Rockenbach, 2014;Mayhew & Bryant Rockenbach, 2012).…”
mentioning
confidence: 99%
“…56 Even when considering these (and other) entering characteristics, nones have the greatest increases in religious Religion/Worldview and Success 121 skepticism and the most pronounced decreases in religious commitment and spiritual identification. 57 They also experience less spiritual struggle and are less committed to their worldview than are religious majority students. 58 These disparities extend beyond spiritual and religious outcomes; nones have the lowest college satisfaction and the greatest declines in subjective well-being, along with the least charitable involvement and compassionate self-concept, of any religion=worldview.…”
Section: Students Identifying With No Organized Religionmentioning
confidence: 99%
“…Bryant et al (2003) observed similar benefits for involvement in religious activities among students attending Protestant institutions. Additional longitudinal research demonstrated that students at non‐Catholic religious institutions had greater gains in spiritual identification and increases in eudaimonic well‐being (living one's life to the fullest) than those at secular schools (Bowman and Small 2010, in press). Students at Adventist Christian colleges scored higher than students at secular colleges on measures of commitment to the church, personal religious commitment, agreement with life‐style standards, and a grace orientation (Dudley 1999).…”
Section: Theoretical Frameworkmentioning
confidence: 99%